Value incorporation in health-unit management: the secret of acceptance - Zoboli, Elma; Fracolli, Lislaine (O Mundo da Saúde, 2006)
Acceptance is proposed as an operational guideline for a health service reorganization aiming to guarantee universal access, fast problem resolution and user-centered assistance. When one goes back to a reflection on universality in assistance and local teams’ governance capacity to intervene in health practices, acceptance catalyzes changes in the way health services are organized. As health assistance occurs inside organizations, the incorporation of acceptance an as strategy for reorganizing health teams work process to focus in the user requires, consequently, the use of direction and management instruments and forms that also prioritize people in the organizational culture and environment. This article aims to retrieve the concept of acceptance in the humanizing policy proposal for health units and to present the general lines of value-centered management central points, searching a way to show a possible integra- tion between the two proposals.